2020
DOI: 10.1111/jth.14826
|View full text |Cite
|
Sign up to set email alerts
|

Combination of cyclic nucleotide modulators with P2Y12 receptor antagonists as anti‐platelet therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this way, when platelet cyclic nucleotide levels are elevated, as may well be the case within the circulation where platelets are bathed in NO and PGI 2 , the antiplatelet effects of P2Y 12 inhibition are greatly potentiated. This synergistic relationship holds clear clinical relevance as a therapeutic target, as we have recently demonstrated by coupling the P2Y 12 antagonist prasugrel with sGC stimulators (Armstrong et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In this way, when platelet cyclic nucleotide levels are elevated, as may well be the case within the circulation where platelets are bathed in NO and PGI 2 , the antiplatelet effects of P2Y 12 inhibition are greatly potentiated. This synergistic relationship holds clear clinical relevance as a therapeutic target, as we have recently demonstrated by coupling the P2Y 12 antagonist prasugrel with sGC stimulators (Armstrong et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…We have previously shown that P2Y 12 receptor antagonists in vitro only weakly inhibit thrombin-or collagen-induced platelet aggregation (Armstrong et al, 2011;Kirkby et al, 2013), however, their effect is strongly related to cyclic nucleotide levels in platelets (Knowles & Warner, 2019). In this way, when platelet cyclic nucleotide levels are elevated, as may well be the case within the circulation where (Armstrong et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation